Neurocognitive and emotional factors predict pain‐related healthcare utilization in children with sickle cell disease. Issue 6 (7th April 2023) - Hardy, Steven J.; Williams, Zaria; Berger, Carly; Griffin, Danielle; Weisman, Hannah; Liang, Hua; Darbari, Deepika S.
Abstract: Background: Youth with sickle cell disease (SCD) experience increased rates of neurocognitive and emotional difficulties. Cross‐sectional studies suggest neurocognitive and emotional functioning are associated with health outcomes in SCD. We investigated whether neurocognitive and emotional factors predicted future pain‐related healthcare utilization in children with SCD. Procedure: Total 112 youth with SCD between ages 7 and 16 years reported sociodemographics and completed measures of neurocognitive functioning and emotional well‐being. The number of emergency department (ED) visits and hospitalizations for pain 1 and 3 years after enrollment were determined by chart review. Results: The mean age of participants was 10.61 years (standard deviation = 2.91), with most being female ( n  = 65; 58%). Eighty‐three (74%) participants had either HbSS or HbSβ 0 thalassemia. Regression analyses showed that attention significantly predicted ED visits and hospitalizations for pain at 1 and 3 years after enrollment (all p ‐values ≤ .017), such that poorer attention was associated with higher healthcare utilization. Lower emotional quality of life also predicted more ED visits for pain at 3 years ( b  = −.009, p  = .013) and hospitalizations for pain at 3 years ( b  = −.008, p  = .020). Conclusions: Neurocognitive and emotional factors are associated with subsequent healthcare use in youth with SCD. Poor attentional control might limit implementation of strategies to distract from pain or could make disease self‐management behaviors more challenging. Results also highlight the potential impact of stress on pain onset, perception, and management. Clinicians should consider neurocognitive and emotional factors when developing strategies to optimize pain‐related outcomes in SCD.